Analytical study and application of new chelating polymers for removal of heavy metals from wastewater sample - Shibli, Rana T.; Jassim, Tarik E. (Mesopotamian Journal of Marine Sciences, 2021)
This study includes the preparation of new Schiff-base derived from (3-amino phenol) and (2-hydroxy benzaldehyde and (2-hydroxy-3-methoxy benzaldehyde), the characterization of this bases is carried out by FT-IR and 1H-NMR The prepared bases were loaded on Urethane foam to prepare chelating polymers which were characterized by FT-IR, TGA and DSC technique. The loading efficiency of these resins were investigated toward several ions Cu+2, Cd+2, Ni+2 and pb+2 in different time and pH by Batch method. The prepared chelating polymers showed a good efficiency towards the studied ions and it was maximum for (Cu+2) ions, An application to prepared chelating polymers was carried out on a sample of wastewater of Hamdan´s station in Basrah South of Iraq, and the results showed high and accurate level efficiency to remove the heavy elements.